THE INFLUENCE OF LEVERAGE, CAPITAL INTENSITY, AND FISCAL LOSS COMPENSATION ON EFFECTIVE TAX RATE - Yunan, Nadiya (Universitas Ibn Khaldun Bogor, 2023)
The purpose of this research is to see how leverage, capital intensity, and fiscal loss compensation affect the effective tax rate. Research methodology: leverage, capital intensity, and fiscal loss compensation are associated with the effective tax rate with agency theory. because of the intervention of the management to take advantage of the situation to reduce the tax burden. Using samples from manufacturing businesses in the primary and chemical industries sub-sector from 2017 to 2020, this study employs multiple regression analysis. leverage has a beneficial influence on tax avoidance. Capital intensity and fiscal loss compensation hurt tax avoidance. This study shows the value of the coefficient of determination (R) is relatively small, so the rest is 72.6% so that other variables can be added. The fiscal loss compensation variable can be used as a moderating variable because it shows significant results and is an external variable. For the Director General of Taxes (DGT), it can be a reference for the weaknesses of laws that companies often use to avoid tax.